Perceptions towards research data sharing: A qualitative study of Nigerian academics - Abdullahi, Khalid Ayuba; Noorhidawati, A. (Malaysian Journal of Library and Information Science, 2020)
Open science provides transparency to research processes by means of open data as data sharing initiates. The need for data sharing among scholars and researchers was evident, the uptake however is slow due to the benefits and detriments of the practices. This paper explores the perceptions of Nigerian academics towards research data sharing practices. Participants from five universities in Nigeria were purposively sampled. Data were gathered through interviews with 22 participants. Their perception towards data sharing was reflected through their awareness, understanding and familiarity of the practice. Most of the participants perceived that data sharing would add value to their professional reputation and fast-track their research progression, however a few of them perceived data sharing as disquieting. The academics labelled data privacy and cultural orientation to be those risks associated with data sharing. The study provides deeper understanding of data sharing and the opportunity for academics to know diverse insights of data sharing practices that would guide scholars in intensifying a variety of data management services, which then can be personalized to their exclusive needs. Further investigation could be done through quantitative research approach to inform data sharing behavior in a larger scale in order to improve the current practices.